A Cross-Level Study on Family Involvement and Job Satisfaction - Wei, Hongguo; Zhu, Jinqiang; Li, Hai; Bilimoria, Diana (Frontiers in Psychology, 2018)
This study aims to explore how various dynamics of working couples’ family involvement shape their job satisfaction. With a sample collected from primary school teachers and spouses in China (n=236), we use polynomial regression, response surface method, and multilevel structural equation model to capture the various dynamics of working couples’ family involvement. We found that 1) high-high spouses’ family involvement has a negative impact on individual job satisfaction, and low-low spouses’ family involvement is positively related to individual job satisfaction. 2) High-high spouses’ family involvement benefits the creation of positive affect at the family level, which decreases family-to-work conflict and mitigates its negative impacts on individual job satisfaction. 3) The working couple’s perceived work-to-family enhancement moderates the relationship between spouses’ family involvement and positive affect at the family level. This study extends our understanding of family-to-work spillover effects from the viewpoint of the dynamic interaction between spouses at the cross level.